NILAI PENDIDIKAN ISLAM TOKOH SRINTIL DALAM NOVEL RONGGENG DUKUH PARUK - Faiz Abdullah; Hamdan Adib; M Misbah (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2021)
The purpose of this research is to describe and identify the value of Islamic education displayed by the character Srintil in the novel Ronggeng Dukuh Paruk. In order to obtain this information, the researcher used a qualitative approach in the type of library research. Where the researcher will collect data related to the novel Ronggeng Dukuh Paruk by Ahmad Tohari as the primary source and supporting studies as the secondary source. The results of this study are the value of Islamic education contained in the novel Ronggeng Dukuh Paruk by Ahmad Tohari in Srintil, namely the value of patience which is implemented in the concept of nrimo which is embedded in Srintil facing the pain of her life line, then caring for parents is shown by taking care of her grandmother who already senile with no sense to be reciprocated he takes care of grandmother as well as possible.